Pengolahan Limbah Air Domsetik: Tinjauan Metode dan Implementasi - Hair Djunur, Lutfi; Virlayani, Asnita; Magfirah, Nurul (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Domestic wastewater from residential areas is a significant source of environmental pollution. Daily activities such as washing, bathing, and defecating produce wastewater containing organic matter, nutrients, and pathogens. If not properly treated, domestic wastewater can cause environmental pollution, public health problems, and ecosystem damage. Therefore, effective domestic wastewater treatment is necessary to mitigate these negative impacts. Domestic wastewater treatment can be carried out using physical, chemical, and biological methods. This article discusses various domestic wastewater treatment methods, including physical, chemical, and biological treatment, as well as the implementation of effective and efficient domestic wastewater treatment systems to help reduce environmental pollution and improve public health.